2018
DOI: 10.1080/22423982.2018.1456303
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutants and haematological markers in Greenlandic pregnant women: the ACCEPT sub-study

Abstract: The Arctic populations have high blood concentrations of persistent organic pollutants (POPs). Exposure to POPs was related to adverse health effects e.g. immune, neurological and reproductive systems. This study investigates associations between serum POP levels and haematological markers in Greenlandic pregnant women. This cross-sectional study included 189 women enrolled in 2010–2011 at the Greenlandic West coast by the inclusion criteria ≥18 years of age and had lived for 50% or more of their life in Green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…There exists a negative association between platelet number (PLT) and size (MPV), which represents PLT and MPV having signi cant association [20,21]. Evidence from previous epidemiological studies reported that the pollutant exposures were positively associated with MPV, PDW, and P-LCR and negatively associated with PLT [22][23][24][25]. Compared to CIA, signi cant differences in CBC parameter levels indicate that pollutant exposure in non-CIA might exist.…”
Section: Discussionmentioning
confidence: 99%
“…There exists a negative association between platelet number (PLT) and size (MPV), which represents PLT and MPV having signi cant association [20,21]. Evidence from previous epidemiological studies reported that the pollutant exposures were positively associated with MPV, PDW, and P-LCR and negatively associated with PLT [22][23][24][25]. Compared to CIA, signi cant differences in CBC parameter levels indicate that pollutant exposure in non-CIA might exist.…”
Section: Discussionmentioning
confidence: 99%
“…Adjustments for POPs were not conducted in this study but should be considered for future studies. Adverse health effects associated with POPs in pregnant Inuit women, the fetus, and newborn are found in several studies [2,23,27,30,32,50,99,100]. The Arctic populations have some of the highest levels of POPs globally [1].…”
Section: Discussionmentioning
confidence: 99%
“…A Danish- and Greenlandic-speaking medical doctor recruited the participants in 2010–2011 and Greenlandic midwives and the study research team in 2013–2015. Enrolment and inclusion to the ACCEPT study have previously been reported [23,27,28,34]. Data on the women’s height (in meters), weight (in kilograms), smoking, and alcohol intake were obtained from medical records.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations